Calidad de vida y el rendimiento académico en jóvenes estudiantes de Caldas, Colombia: estudio piloto (Investigaciones) - Saéz Abello, Guillermo Andrés (2024)
In recent years, literature has been examining the concept of quality of life from various perspectives, circumstances, contexts, and populations, all with the aim of understanding how this construct influences different areas of life, including academic performance. We aimed to determine the relationship between overall quality of life, health-related quality of life, and their dimensions with academic performance in young students. We used a quantitative, descriptive-correlational study with a cross-sectional design conducted among a population of students residing in the department of Caldas, Colombia. The WHOQOL-BREF scale was used to measure quality of life, and participants were asked to provide their cumulative grade point average from the previous semester or period for the evaluation of academic performance. All data were analyzed using SPSS 25, including tests for normality, measures of central tendency and dispersion, as well as Spearman correlation tests. Positive relationships were identified in most variables, with the only negative correlation observed in the social domain. Two positive and statistically significant relationships were highlighted in the environmental and psychosocial domains. The young participants reported satisfactory scores in selfperceived overall quality of life and health-related quality of life. The academic performance was 3,6 ± 0,49. There is no significant correlation between quality of life, health-related quality of life, and academic performance. On the other hand, a positive and significant relationship was identified between the environmental and psychosocial domains and academic performance, suggesting that greater satisfaction with environmental conditions and good psychological health could favor academic performance.